2016
DOI: 10.1111/are.13134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurine enrichment in rotifer ( Brachionus sp.) on growth of larvae of Pacific bluefin tuna Thunnus orientalis (Temminck & Schlegel) and yellowfin tuna T. albacares (Temminck & Schlegel)

Abstract: To investigate the dietary effect of taurine on the larval stage of tuna species, Pacific bluefin tuna (PBF) and yellowfin tuna (YFT), larvae were reared until 16 days after hatching (dAH) and 14 dAH, respectively, and replicate samples were fed either non-taurine-enriched rotifers (T-0) or rotifers enriched with 800 mg taurine L À1 (T-800). Most PBF and YFT larvae were at the preflexion stage until 7 and 8 dAH, and there were no differences in the growth performance and total protein content of larvae between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
2
8
0
1
Order By: Relevance
“…In order to confirm an active role for taurine metabolism including biosynthesis in ABT, a trial was carried out by feeding larvae from mouth opening to 14 dah with different levels of taurine supplied via rotifers enriched with increasing levels of taurine. Taurine concentration in larvae was strongly correlated to the level of taurine enrichment in rotifer in agreement with previous trials (Matsunari et al, 2007;Katagiri et al, 2017;Koven et al, 2018). This confirms that ABT larvae are able to assimilate dietary taurine into their tissues and may reflect a taurine requirement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In order to confirm an active role for taurine metabolism including biosynthesis in ABT, a trial was carried out by feeding larvae from mouth opening to 14 dah with different levels of taurine supplied via rotifers enriched with increasing levels of taurine. Taurine concentration in larvae was strongly correlated to the level of taurine enrichment in rotifer in agreement with previous trials (Matsunari et al, 2007;Katagiri et al, 2017;Koven et al, 2018). This confirms that ABT larvae are able to assimilate dietary taurine into their tissues and may reflect a taurine requirement.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, a recent study in Pacific bluefin (Thunnus orientalis) and yellowfin tuna (T. albacares) larvae demonstrated that feeding rotifers enriched with 800 mg taurine L -1 promoted larval growth and total protein content (Katagiri et al, 2017), suggesting that taurine is an important nutrient for the early stages of rapidly growing teleost species.…”
Section: Introductionmentioning
confidence: 99%
“…However, not only lipids and essential fatty acids, but other nutrients such as antioxidants (vitamin E, vitamin C and Se) and taurine, have been proposed as essential components for fast growing marine fish species, particularly in tuna which cannot synthesize these compounds (Yokohama et al, 2001;Waagbø, 2010;NRC, 2011;Izquierdo and Betancor, 2015;Katagiri et al, 2016). Indeed, growth in fish is primarily due to protein deposition with most marine fish larvae having a high requirement for essential amino acids (Rønnestad et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Live foods that are commonly used for larval marine fish rearing (including tunas), such as rotifers (Brachionus sp. ), have naturally low levels of essential fatty acids (Maehre et al, 2013;Takeuchi, 2014;Kostopoulou et al, 2015), vitamins E and C, Se, iodine (Hamre et al, 2008;2013), taurine (Takeuchi, 2014;Katagiri et al, 2016) and essential amino acids (Rajkumar and Kumaraguru vasagam, 2006), especially when compared with copepods, the natural prey of tuna larvae (van der Meeren et al, 2008;Maehre et al, 2013). In this context, successful larval production of marine fish depends upon the supply of live feed fortified with the essential nutrients that are insufficient in the live feeds.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment can increase the fatty acid content and other essential nutrients of live feeds, which are crucial to the development of fish larvae (Li & Olsen, ; Morais & Conceição, ). The inclusion of the organic acid taurine in live feeds has been shown to be effective in enhancing the growth of fish larvae of a variety of species (Katagiri et al, ; Kim et al, ; Matsunari et al, ; Partridge & Woolley, ). Microbound diets, a potential replacement of live feed, have been developed by many researchers and used to partially replace the live feed without affecting the survival rate and growth of Japanese flounder larvae (Kanazawa, Koshio, & Teshima, ; Takeuchi et al, ; Teshima, Koshio, Ishikawa, Alam, & Hernandez, ).…”
Section: Introductionmentioning
confidence: 99%